2017
DOI: 10.1111/sed.12333
|View full text |Cite
|
Sign up to set email alerts
|

Response of unconfined turbidity current to normal‐fault topography

Abstract: Turbidity currents descending the slopes of deep‐water extensional basins or passive continental margins commonly encounter normal‐fault escarpments, but such large‐magnitude phenomena are hydraulically difficult to replicate at small scale in the laboratory. This study uses advanced computational fluid dynamics numerical simulations to monitor the response of large, natural‐scale unconfined turbidity currents (100 m thick and 2000 m wide at the inlet gate) to normal‐fault topography with a maximum relief of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(80 citation statements)
references
References 90 publications
3
72
0
Order By: Relevance
“…Detailed bathymetric maps and corresponding interpretations of seafloor structures to indicate the relative age relationships between bedforms, see index map in bottom right for locations. A hydraulic jump zone may develop at the toe, scouring sedimentary beds at the foot of the escarpment(Breda et al, 2007;Ge et al, 2017), a process similar to the Detailed bathymetric maps, corresponding interpretations, and bathymetric-topographic cross sections of seafloor structures in the study area, see index map on right side for locations. (b) Mudflow deposits with furrowed surfaces overlain by younger mudflow deposits without furrows and sediment waves on the caldera floor; note gryphon-cone in top right corner.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Detailed bathymetric maps and corresponding interpretations of seafloor structures to indicate the relative age relationships between bedforms, see index map in bottom right for locations. A hydraulic jump zone may develop at the toe, scouring sedimentary beds at the foot of the escarpment(Breda et al, 2007;Ge et al, 2017), a process similar to the Detailed bathymetric maps, corresponding interpretations, and bathymetric-topographic cross sections of seafloor structures in the study area, see index map on right side for locations. (b) Mudflow deposits with furrowed surfaces overlain by younger mudflow deposits without furrows and sediment waves on the caldera floor; note gryphon-cone in top right corner.…”
mentioning
confidence: 73%
“…shown that the deposition of sand may not only occur at the toe of such a morphology but also along the upper edge(Ge et al, 2017). (a) Mudflow deposits with furrowed surfaces overlain by younger mudflow deposits without furrows and bathymetric-topographic cross section of sediment waves on the caldera floor.…”
mentioning
confidence: 99%
“…The flow upper surface concurrently developed a hydraulic instability in the form of backwards‐rolling large Kelvin–Helmholtz (K–H) waves, generated by the interface shear between the flow and the ambient seawater (Britter & Simpson, ; Ge et al ., ; Kostaschuk et al ., ). These internal K–H waves, by propagating concentrically from the flow U‐shaped front, came into interference within the flow (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The turbidity current flow was modelled using the deterministic process modelling CFD software MassFlow‐3D™, which is a customized version of Flow‐3D™ (FlowScience, ; http://www.flow3d.com). The reliability of MassFlow‐3D™ was verified by imitating laboratory and natural‐scale turbidity currents (Heimsund, ; Heimsund et al ., ) and the software has been used extensively to simulate such deep‐water sediment gravity currents (Aas et al ., ,, ; Janocko et al ., ; Basani et al ., ; Ge et al ., , ). The numerical code describes fluid motion by solving the system of Reynolds‐averaged Navier–Stokes (RANS) equations by a finite‐volume finite‐difference method for a 3D computational grid.…”
Section: Methodsmentioning
confidence: 99%
“…() and Ge et al . () use the same model to simulate turbidity currents and can provide further detail.…”
Section: Methodsmentioning
confidence: 99%